2018
DOI: 10.1016/j.jemermed.2018.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Using Serial Hemoglobin Levels to Detect Occult Blood Loss in the Early Evaluation of Blunt Trauma Patients

Abstract: Our results indicated that ΔHgb does not reliably distinguish between blunt trauma patients who require intervention and those who do not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Then, prehospital fluid resuscitation induces further hemodilution and fall in Hct and Hb. Therefore, serial measurements are recommended for the evaluation of trauma-related hemorrhage [18,19], but the results are still controversial [17,20].…”
Section: Introductionmentioning
confidence: 99%
“…Then, prehospital fluid resuscitation induces further hemodilution and fall in Hct and Hb. Therefore, serial measurements are recommended for the evaluation of trauma-related hemorrhage [18,19], but the results are still controversial [17,20].…”
Section: Introductionmentioning
confidence: 99%
“…While there is evidence that a low Hgb level soon after injury can be an indicator of serious ongoing hemorrhage, 4,5 more data have shown that isolated and serial Hgb levels in the initial evaluation of patients confuse the clinical picture and lead to inconsistencies when determining if a patient needs surgical management. [6][7][8][9][10][11][12] In a systematic review looking at prognostic factors for the failure of NOM, Hgb levels did not adequately predict the failure of NOM. 13 According to the Eastern Association for the Surgery of Trauma (EAST), there is not substantial evidence to recommend duration or frequency of hemoglobin measurements for splenic injuries undergoing NOM.…”
Section: Introductionmentioning
confidence: 99%